2013
DOI: 10.1084/jem.20121801
|View full text |Cite
|
Sign up to set email alerts
|

A mutated B cell chronic lymphocytic leukemia subset that recognizes and responds to fungi

Abstract: A subset of chronic lymphocytic leukemia with mutated IGHV-genes express BCRs specific for an antigenic determinant of yeast and filamentous fungi, β-(1,6)-glucan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 51 publications
(78 reference statements)
3
100
0
1
Order By: Relevance
“…2,3,8 The stereotypic V4-59-RFs of HCV lymphomas 103 and 110 were also produced as IgM antibodies, and they did indeed display strong IgG-binding capacity, as previously also shown of a V4-59-RF derived from a CLL, 5 and which is comparable to that of two control lymphoma-derived V1-69-RF IgM antibodies M11 and SG22 originating from Sjögren's syndrome patients.…”
supporting
confidence: 72%
“…2,3,8 The stereotypic V4-59-RFs of HCV lymphomas 103 and 110 were also produced as IgM antibodies, and they did indeed display strong IgG-binding capacity, as previously also shown of a V4-59-RF derived from a CLL, 5 and which is comparable to that of two control lymphoma-derived V1-69-RF IgM antibodies M11 and SG22 originating from Sjögren's syndrome patients.…”
supporting
confidence: 72%
“…It was recently shown that a newly identified subset of CLL with mutated IgVH heavy chain, expresses stereotypic BCRs highly specific for β-(1,6)-glucan, a major antigenic determinant of yeast and molds. 60 The clonal B-cells of these patients were shown to proliferate in response to β-(1,6)-glucan, suggesting that the fungal microbiota can deliver functional ligands in the process of CLL.…”
mentioning
confidence: 93%
“…Furthermore, use of certain V genes (e.g., V1-69, V3-21) or even more specific restricted combinations of V(D)J and light chains are independent poor prognostic factors (16,17), with specific types having distinct gene expression patterns (18). It is postulated that this stereotypy results in surface BCR with specific affinity for immunogen capable of tonically stimulating the BCR, thereby promoting cancer cell survival 19,20). Additionally, there is evidence that certain stereotyped BCRs may be constitutively activated by self-self interaction (21).…”
Section: Discussionmentioning
confidence: 99%